Impacts of organic enrichment on macrobenthic production, productivity, and transfer efficiency: What can we learn from a gradient of sewage effluents?. (September 2022) - Vesal, Seyed Ehsan; Auriemma, Rocco; Libralato, Simone; Nasi, Federica; Negro, Paola Del
Abstract: We studied the macrobenthic invertebrate biomass (B), production (P), productivity (P/B̅-ratio), and transfer efficiency (TE) influenced by sewage effluents discharge in a diffusion zone. Our results indicated a clear distribution pattern of macrofauna communities along the sewage discharge gradient where biological factors (B, P, P/B̅, and TE) were driven by changes observed in community structure, composition, and the influence of environmental variables. The lowest B, P, and P/B̅ were observed at the stations sampled close to the pipelines. Abundance, biomass, production, and productivity increased with increasing distance from the pipelines toward stations placed at 100 m distance and then decreased toward the stations placed at >200 m, where there was a negative relationship between TE and B of macrofauna at sampling stations. Overall, there was a clear influence of the sewage discharge on macrofauna communities, but surrounding environment was influenced moderately by organic impact and discharges had no negative impacts. Highlights: The benthic community was affected moderately by organic impact. Production and productivity displayed higher values at 100 m distance. Analyses distinguished a negative relationship between transfer efficiency and biomass. Biomass was lowest values at the high impacted stations situated at <5 m distance. The highest values of transfer efficiency were observed at the high impacted stations.